Pengembangan Media Pembelajaran Interaktif Berbantuan Aplikasi Assemblr Edu pada Materi Teks Eksplanasi untuk Meningkatkan Higher-Order Thinking Skills (HOTS) Siswa Kelas XI - Mifta Aulia Putri; Rita Rita; Ridwan Syahputra; Rika Kartika; Ratna Soraya (Medan Resource Center, 2026)
This study aimed to develop interactive learning media assisted by the Assemblr Edu application for explanation text instruction to support the improvement of students’ Higher-Order Thinking Skills (HOTS). The study addressed the need for innovative digital learning media capable of promoting more active, engaging, and higher-level thinking-oriented learning in Indonesian language classrooms. This research employed a Research and Development (R&D) approach using the ADDIE model, consisting of the Analysis, Design, Development, Implementation, and Evaluation stages. The population comprised 120 eleventh-grade students of SMKS MMA UISU Medan from the XI-AKL, XI-OTKP, and XI-TKJ classes, while the sample consisted of 43 students from class XI-OTKP. Data were collected through observation, questionnaires, and tests. The findings revealed that the developed interactive learning media was categorized as feasible based on material expert validation (87% and 92%), media expert validation (87% and 80%), and teacher assessment (90%). The field implementation involving 43 students obtained a feasibility score of 82.2%, while the effectiveness test reached 77.79%, indicating that the media was effective. These findings demonstrate that the Assemblr Edu-assisted interactive learning media is feasible and effective for explanation text instruction while providing a technology-based learning environment that supports the development of students’ Higher-Order Thinking Skills (HOTS).